(untitled) (Bangladesh Journal of Medical Science, 2017)
Asynchronous bilateral ovarian torsion is uncommon, but a potential possibility. Delayed intervention of the same may even result in castration. Being torsion conscious helps early diagnosis before necrosis of the ovary and permits conservative management. Bilateral ovarian fixation at initial surgery may prevent recurrence on either side. Bangladesh Journal of Medical Science Vol.16(3) 2017 p.452-454